2002
DOI: 10.1152/ajpendo.00458.2001
|View full text |Cite
|
Sign up to set email alerts
|

Increase in daily LH secretion in response to short-term calorie restriction in obese women with PCOS

Abstract: . Increase in daily LH secretion in response to short-term calorie restriction in obese women with PCOS. Am J Physiol Endocrinol Metab 282: E865-E872, 2002. First published December 11, 2001 10.1152/ajpendo.00458.2001We hypothesized that short-term calorie restriction would blunt luteinizing hormone (LH) hypersecretion in obese women with polycystic ovary syndrome (PCOS) and thereby ameliorate the anovulatory endocrine milieu. To test this hypothesis, 15 obese patients with PCOS and nine age-and body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 64 publications
0
23
0
1
Order By: Relevance
“…SHBG was improved in all of the longer term studies, with only one veryshort-term intervention failing to show improvement (86). Clinically, improvements in hirsutism were documented in a number of studies (87,88,89). Menstrual function and ovulation improved in all the studies reporting this endpoint.…”
Section: Lifestyle Intervention and Weight Lossmentioning
confidence: 89%
“…SHBG was improved in all of the longer term studies, with only one veryshort-term intervention failing to show improvement (86). Clinically, improvements in hirsutism were documented in a number of studies (87,88,89). Menstrual function and ovulation improved in all the studies reporting this endpoint.…”
Section: Lifestyle Intervention and Weight Lossmentioning
confidence: 89%
“…The results of validation experiments strongly support the use of deconvolution as an accurate approach to assessment of endogenous FFA release, similar to its exploitation for release of various hormones. (28)(29)(30)(31)). Yet it must be noted that FFA pulses in the validation experiments were simulated by infusion of octanoate, a medium-chain fatty acid that has the advantage of superior aqueous solubility but is certainly not representative of the physiological spectrum of FFAs in vivo, which are mainly…”
Section: Discussionmentioning
confidence: 99%
“…Acien and colleagues 39 and Meirow and colleagues 40 reported that approximately 10% of patients with PCOS and no obesity could present insulin resistance. Weight reduction in these patients is accompanied by an increase in insulin sensitivity [41][42][43][44] followed by association of hyperandrogenism and restored ovulation, [45][46][47][48][49] although the diet abandonment rate in these women owing to lack of motivation due to difficulty in achieving significant weight loss is high. This lack of adherence to diets and abandonment were the main reasons for using drugs to induce ovulation and achieve pregnancy.…”
Section: Insulin Sensitizersmentioning
confidence: 99%